2015
DOI: 10.1016/j.molonc.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Src family kinases differentially influence glioma growth and motility

Abstract: Src-family kinase (SFK) signaling impacts multiple tumor-related properties, particularly in the context of the brain tumor glioblastoma. Consequently, the pan-SFK inhibitor dasatinib has emerged as a therapeutic strategy, despite physiologic limitations to its effectiveness in the brain. We investigated the importance of individual SFKs (Src, Fyn, Yes, and Lyn) to glioma tumor biology by knocking down individual SFK expression both in culture (LN229, SF767, GBM8) and orthotopic xenograft (GBM8) contexts. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 49 publications
5
51
0
Order By: Relevance
“…36 The lack of a clinical benefit was considered to be a potential result of the different molecular profiles of dasatinib targets between archival tumor resected at the time of the diagnosis of GBM and the profile at disease recurrence; it also was noted that response to dasatinib in patients with GBM may require driver mutations in dasatinib targets. 37 Consistent with this, higher levels of LYN expression were correlated with both a PFS6 and OS advantage in the current study, regardless of treatment. The results indicate that individual SFKs (Src, Fyn, YES, and LYN) differ significantly with regard to their importance for glioma growth and motility, and the efficacy of dasatinib therapy may depend on the relative expression of particular SFKs.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…36 The lack of a clinical benefit was considered to be a potential result of the different molecular profiles of dasatinib targets between archival tumor resected at the time of the diagnosis of GBM and the profile at disease recurrence; it also was noted that response to dasatinib in patients with GBM may require driver mutations in dasatinib targets. 37 Consistent with this, higher levels of LYN expression were correlated with both a PFS6 and OS advantage in the current study, regardless of treatment. The results indicate that individual SFKs (Src, Fyn, YES, and LYN) differ significantly with regard to their importance for glioma growth and motility, and the efficacy of dasatinib therapy may depend on the relative expression of particular SFKs.…”
Section: Discussionsupporting
confidence: 88%
“…35 Recent clinical research investigating dasatinib monotherapy in patients with recurrent GBM reported a PFS6 of only 6%, despite efforts to enrich the patient population and to increase the dose of dasatinib, however. 37 It is interesting to note that depletion of LYN resulted in increased tumor growth and reduced OS in these orthotopic, patientderived GBM xenografts, suggesting a tumor suppressor function for LYN in GBM. The strategy of targeting SFK signaling has been studied recently in culture and orthotopic xenograft models.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Several in-vitro studies showed that FYN knockdown is associated with decreased cell migration and proliferation of glioma cells 3,8,9 . Nevertheless, in vivo human glioma xenograft models of FYN Knockdown in immune-suppressed animals failed to show any difference in survival 8 . Therefore, an immune-competent mouse model that enables the generation of FYN knockdown gliomas amenable for understanding the mechanism of anti-glioma immune response is essential.…”
Section: Introductionmentioning
confidence: 99%